Modernization of Religious Courts: An Analysis of the Effectiveness of Mediation Through E-Court in Resolving Divorce Cases in Padang - Firdaus, Firdaus; Harahap, Titi Martini; Sasralina, Rika; Syamsurizal; Zhuliansyah, Teddy Rahmat (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2024)
This study is important to understand the effectiveness of e-Court in handling divorce cases involving mediation, especially in the Class 1A Religious Court of Padang. Although e-Court has improved administrative efficiency and access, there are gaps in the effectiveness of online mediation, especially in cases involving emotional conflict or domestic violence. These limitations indicate the need for a more in-depth approach to addressing the emotional dimension in the e-Court process as well as improving technical support and staff competence. The object of this study is e-Court as a means of divorce proceedings, with a focus on analyzing the effectiveness of the legal process in cases requiring mediation. This study uses a qualitative descriptive method through in-depth interviews and observations. Primary data were obtained from key informants such as judges, e-Court employees, advocates, and the community, while secondary data were taken from related literature. The findings show that e-Court is effective in terms of ease of access, process efficiency, decision quality, and user satisfaction. Although technological infrastructure supports accessibility, improvements in internet access are still needed. E-Court reduces case handling time, but physical interaction is still needed. User satisfaction is high, although there are complaints about the system sometimes experiencing errors, as well as the need for further training for employees to improve competence.